Regional Geology: A Case-Based Approach - Graham, Calvin (Brooklyn: States Academic Press, 2023)
Regional geology is the geological study of large-scale regions. This area of study creates an important connection between local and global geology. The occurrence of geological processes and geologically significant boundaries help define the size and borders of each region. The objective of regional geology is to simplify local surface and subsurface data to a scale that helps in predicting and highlighting the generalizations that are implicit in continent-wide and global syntheses. Regional geology establishes the association among global plate tectonics, global climate changes, sea-level changes, and important studies in geoscience. It is applied in the search and conservation of natural resources such as water, ore deposits, and solid Earth energy resources. This book outlines the major concepts of regional geology in detail. Those in search of information to further their knowledge will be greatly assisted by this book.
Includes index
Keywords: Regional geology; Stratigraphic Geology; Geology$1 (BCase studiess; Tectonics; Geological mapping